Core stabilization exercise can improve lumbar joint position sense in healthy individuals - Prasertkul, Wallika; Thawalyawichachit, Laddawan; Wattananon, Peemongkon (Journal of Associated Medical Sciences, 2025)
Background: Core stabilization exercises (CSE) are based on motor learning concepts focusing on sensorimotor function. It has been proposed that CSE can improve core stabilizer muscle function, leading to enhanced joint position sense. However, evidence to support the effects of CSE on joint position sense is still limited. Objective: To compare the immediate effect of CSE on joint position sense of the lumbar spine using a smartphone application in healthy individuals. Materials and methods: Fifty-six healthy individuals (9 males and 47 females) were recruited in the study. Two smartphones with the application were attached to the lumbar spine (L1) and sacrum (S2). They were asked to perform 45-degree lumbar flexion and return to neutral position, while lumbar joint position errors were recorded in each direction. They were then randomly assigned to CSE and control groups. After the intervention, they were asked to perform 45-degree lumbar flexion and return to a neutral position. Results: The CSE group demonstrated significant improvement (p<0.05) in lumbar joint position sense during the 45-degree flexion, whereas the control group did not show improvement. Both groups did not show significant improvement during the return to a neutral position. Conclusion: Findings suggested that one session of the CSE can improve lumbar joint position sense, which could be due to the increased activities of muscle spindles and Golgi tendon organs. In addition, our findings support the clinical utility of this smartphone application in measuring lumbar joint position sense.